Chromosomal Aberrations and Schizophrenia: Autosomes - Bassett, Anne S. (1992)
Chromosomal aberrations associated with schizophrenic disorders may suggest regions in which to focus a search for genes predisposing to schizophrenia by a linkage strategy. As for other genetic illnesses, chromosomal abnormalities may also provide useful tools for subsequent physical mapping, fine localisation, and isolation of important susceptibility genes. Identification of several chromosomal aberrations may be especially important, given the unknown pathophysiology, the paucity of known brain genes, and the probable genetic heterogeneity of schizophrenia and manic-depression. However, because psychiatric disorders are common and inherited in a complex manner, researchers must use caution when drawing inferences about associations with chromosomal aberrations. Reported abnormalities involving autosomes (chromosomes 1 –22) associated with psychotic disorders are reviewed. Their relevance to linkage studies localising genes for schizophrenia was estimated by standardised criteria for specificity, diagnosis, family history, and overall weight of evidence. Four ‘possibly relevant’ chromosomal regions were identified: 5q, 11q, 18q, and 19p. This paper outlines strategies for future studies to detect new chromosomal aberrations associated with major psychotic disorders that may be relevant to isolating the genes for schizophrenia.